2004
DOI: 10.3748/wjg.v10.i6.783
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor C and chemokine receptor CCR7 in gastric carcinoma and their values in predicting lymph node metastasis

Abstract: AIM:To study the expression of vascular endothelial growth factor C (VEGF-C) and chemokine receptor CCR7 in gastric carcinoma and to investigate their associations with lymph node metastasis of gastric carcinoma and their values in predicting lymph node metastasis. METHODS:The expression of VEGF-C and CCR7 in gastric carcinoma tissues obtained from 118 patients who underwent curative gastrectomy was examined by immunohistochemistry. Among these patients, 39 patients underwent multi-slice spiral CT (MSCT) exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
2
33
1
Order By: Relevance
“…CCL21 (6Ckine, SLC) is a chemokine thought to be involved in recruitment of T cells and dendritic cells to lymph nodes and is expressed by the lymphatic vessels of many tissues (Gunn et al, 1998;Saeki et al, 1999). Recent reports have also shown that human (Takeuchi et al, 2004) and murine (Wiley et al, 2001) melanomas express CCR7, the receptor for CCL21 and CCL19 and that in gastric carcinoma, head and neck squamous cell carcinoma, non-small cell lung cancer and breast cancer these two factors may be associated with lymph node metastasis (Muller et al, 2001;Mashino et al, 2002;Takanami, 2003;Wang et al, 2004;Yan et al, 2004). In the present study, we showed that two different malignant melanoma cell lines can detect CCL21 in vitro through expression of its cognate receptor CCR7 on melanoma cells, as a result of which the melanoma cells migrated towards the source of the chemokine.…”
Section: Discussionmentioning
confidence: 99%
“…CCL21 (6Ckine, SLC) is a chemokine thought to be involved in recruitment of T cells and dendritic cells to lymph nodes and is expressed by the lymphatic vessels of many tissues (Gunn et al, 1998;Saeki et al, 1999). Recent reports have also shown that human (Takeuchi et al, 2004) and murine (Wiley et al, 2001) melanomas express CCR7, the receptor for CCL21 and CCL19 and that in gastric carcinoma, head and neck squamous cell carcinoma, non-small cell lung cancer and breast cancer these two factors may be associated with lymph node metastasis (Muller et al, 2001;Mashino et al, 2002;Takanami, 2003;Wang et al, 2004;Yan et al, 2004). In the present study, we showed that two different malignant melanoma cell lines can detect CCL21 in vitro through expression of its cognate receptor CCR7 on melanoma cells, as a result of which the melanoma cells migrated towards the source of the chemokine.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that normal chemokine signalling pathways that play a central role in lymphoid cell migration and homeostasis can be subverted in SCCHN (and other tumours) to mediate specific patterns of tumour spread. CC chemokine receptor 7 is known to influence the migration of activated dendritic cells to regional lymph nodes and appears to play a similar role in gastric, oesophageal and head and neck cancers (Mashino et al, 2002;Ding et al, 2003;Wang et al, 2004;Yan et al, 2004). Mashino et al (2002) showed that 66% of gastric carcinoma samples from 64 patients expressed CCR7 and those patients with CCR7-positive tumours had a significantly worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have demonstrated that CCR7 appears to play an important role in the development of lymph node metastases from oesophageal and gastric cancers (Mashino et al, 2002;Ding et al, 2003;Yan et al, 2004). CC chemokine receptor 7 is also expressed by human adult T-cell leukaemia cells that lodge in lymph nodes (Hasegawa et al, 2000).…”
mentioning
confidence: 99%
“…Numerous studies have shown that CCR7 is differentially expressed in tumor cells in gastric cancer at the mRNA and protein levels, as well as in the cell membrane in vitro and in vivo (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). In addition, CCR7 was detected in tumor-infiltrating lymphocytes and dendritic cells in gastric cancer, as well as in mononuclear cells in Helicobacter pylori gastritis (35,38).…”
Section: C-c Motif Ccr7mentioning
confidence: 99%